Characterization of concrete composites with recycled plastic aggregates from postconsumer material streams. (10th September 2018) - Jacob-Vaillancourt, Colin; Sorelli, Luca
Highlights: Optical sorting allowed to reduce the impurity of sorted plastic to about 5% A fifth of the aggregate of concrete can be replaced with plastics from postconsumer material streams. Comparing different plastics, PVC allowed the lowest reduction of compressive strength. PAG allowed to increase thermal insulation of 5% and reduce water adsorption. The seasonal variations had an acceptable impact on concrete performances. The presence of surface contamination and entrapped air are critical factors to consider. Correlation analysis showed the importance of bulk density and PAG shape. Abstract: Plastic waste is today an crucial environmental issue for which innovative recycling techniques are needed. This research aims at investigating the feasibility of replacing fine aggregate in concrete by recycled plastics from real post-consumer streams. Different kind of plastics were sorted in Material Recovery Facilities (MRF) to realize different Plastic Aggregates (PAG) at different seasonal time. The concrete composites were characterized in terms of compressive strength, post-cracking compressive strength, toughness indeces, thermal conductivity, density, and water absorptivity. Correlation tables were used to understand the key material parameter of PAG governing concrete properties. The effects of the replacement percentage, the PAG kind, the level of impurity, and the time-related variations on the quality of the concrete are discussed. The presented results indicate that concrete composite with PAG from postconsumer waste is a promising research direction for developing eco-responsible construction materials with enhanced thermal insulation and water absorptivity.